Legal Counseling on Radicalism - Bima, Muhammad Rinaldy; Aswari, Aan (Advances in Community Services Research, 2025)
Purpose: This study aims to explore the increasing vulnerability of young individuals to radicalization and terrorist recruitment, mainly through social media. The study focuses on the lack of awareness among local communities and village officials regarding radicalism and examines preventive measures through legal counseling and digital literacy programs. The research was conducted in Pucak Village, Tompobulu District, and Maros Regency, where concerns about radical influences remain significant. Research Design and Methodology: A qualitative descriptive approach is employed to analyze the patterns of radical recruitment, the role of terrorist networks, and the effectiveness of government surveillance and legal intervention. Data collection includes direct observations, interviews with community members and officials, and documentation of legal awareness initiatives. The study also evaluates digital education strategies aimed at preventing online radicalization. Findings and Discussion: The findings indicate that village officials and the local community have limited knowledge of radicalism, making them vulnerable to indirect involvement in radical activities. Additionally, inadequate digital literacy and ineffective government oversight contribute to the spread of radical ideologies. Collaborative strategies involving law enforcement, cybersecurity agencies, and community engagement are necessary for preventing radical influence. Implications: The study suggests that preemptive and preventive legal counseling combined with enhanced digital literacy can significantly reduce radical influence. Strengthening community awareness programs and law enforcement coordination is crucial in mitigating radicalism in local villages.